Implementation of cognitive and social apprenticeship frameworks to nurture creativity in a social networking site - Abdullah, Zaleha (American Scientific Publishers, 2015)
This study investigates the use of COCIAL framework (cognitive and social apprenticeship) within an educational technology design classroom and in a social network setting—Facebook. Through the implementation of COCIAL, students are exposed to the social construction of thinking influenced by more than one community—the creative industries and the higher education communities. A qualitative research design was utilized and data consisted of online semi-structured questionnaires and face-to-face interviews were analysed. The process of analysis is divided into two stages of initial and substantive of four case studies. The findings of this study contribute to our understanding that the process of creativity can be nurtured within higher education through the use of Facebook and with the implementation of COCIAL framework. Nevertheless, some concerns are also highlighted, in order to determine the success and failure of the approaches